Perlindungan Hukum Terhadap Perempuan Korban Kekerasan Berbasis Gender Online di Indonesia - Stella Hita Arawinda (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2022)
Rapid development of science and technology has become an indicator of disruption era in which innovation and fundamental changes happens. Amidst COVID-19 pandemic enforced the government to limit social mobility and shift all offline activities to online since early 2020 and bring impact in escalating people's access to cyberspace. One of the logical implication is increasing cases of online gender-based violence towards Indonesian women. Referring to definition by the Broadband Commission for Digital Development, online gender-based violence is a technology-facilitated act of gender-based discriminative violence towards certain person and causing traumatic effects. The Annual Record of Violence Against Women issued by Indonesia’s National Commission on Violence Against Women in 2021 stated that the online gender-based violence rise significantly to 699 cases or up to 300% in the past 2 years (2019 until 2020). Based upon this urgency hence formulated a research comprise of: (1) The dynamics of violence against Indonesian women during the COVID-19; (2) Analysis and evaluation of RUU PKS and UU ITE as the legal basis to protect women as victims of online gender-based violence; (3) Optimization of the institution in protection for women as victims of online gender-based violence during pandemic. This research uses normative juridical method with literature study approach. The results are several weaknesses still founded in Indonesia’s legal instruments, especially in UU ITE as Indonesia’s Cyber Law to overcome online gender-based violence. However, RUU PKS will be useful when legalized. As for the existence of legal protection supporting institutions, still needs to be optimized.